AN ANALYSIS OF MARKETING MARGIN AND ELASTICITY OF BELL PEPPER COMMODITY PRICE TRANSMISSION (A STUDY IN CANDIKUNING VILLAGE, BATURITI DISTRICT, TABANAN REGENCY) - Mega Hudha Ayu Lukitasari; I Gusti Ayu Agung Lies Anggreni; Ida Ayu Listia Dewi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
The development of the agribusiness sector does not only focus on marketing but also on production. Tabanan is the leading producer of paprika in Bali. As a horticultural product, paprika has perishable nature, and its price is determined by the quality of the good. Besides, the marketing of horticultural commodities tends to involve many institutions which have an impact on prices in the market due to the distance between production sites and market locations. The purpose of this study were to analyze the marketing channels, market structure, and efficiency in marketing paprika in Candikuning, Baturiti, Tabanan Regency. The research method that been used was descriptive qualitative in marketing channels, price transmission elasticity, marketing margins, distribution of marketing margin, and farmer's share. The result showed that there are seven marketing channels in Candikuning. The market structure formed as imperfect competition market which is showed by the price transmission elasticity was 0.950 (Et <1). The marketing margin with the highest value was Rp 20,878.82/kg while the lowest was Rp 6,412.96/kg. The highest farmer share value was 87.76% while the lowest was 66.92%